Predicting healthcare outcomes in prematurely born infants using cluster analysis. Issue 8 (23rd May 2018) - MacBean, Victoria; Lunt, Alan; Drysdale, Simon B.; Yarzi, Muska N.; Rafferty, Gerrard F.; Greenough, Anne
Abstract: Aims: Prematurely born infants are at high risk of respiratory morbidity following neonatal unit discharge, though prediction of outcomes is challenging. We have tested the hypothesis that cluster analysis would identify discrete groups of prematurely born infants with differing respiratory outcomes during infancy. Methods: A total of 168 infants (median (IQR) gestational age 33 (31‐34) weeks) were recruited in the neonatal period from consecutive births in a tertiary neonatal unit. The baseline characteristics of the infants were used to classify them into hierarchical agglomerative clusters. Rates of viral lower respiratory tract infections (LRTIs) were recorded for 151 infants in the first year after birth. Results: Infants could be classified according to birth weight and duration of neonatal invasive mechanical ventilation (MV) into three clusters. Cluster one (MV ≤5 days) had few LRTIs. Clusters two and three (both MV ≥6 days, but BW ≥or <882 g respectively), had significantly higher LRTI rates. Cluster two had a higher proportion of infants experiencing respiratory syncytial virus LRTIs ( P  = 0.01) and cluster three a higher proportion of rhinovirus LRTIs ( P  < 0.001) Conclusions: Readily available clinical data allowed classification of prematurely born infants into one of three distinct groups with differing subsequent respiratory morbidity in infancy.